2007
DOI: 10.4049/jimmunol.178.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Type B T Cells after Protein Immunization Reveals Novel Pathways of In Vivo Presentation of Peptides

Abstract: Type B T cells recognize a peptide-MHC conformer generated in recycling endosomes and eliminated by H2-DM in late endosomes; as a result, they recognize exogenous peptide, but fail to respond to the identical epitope generated from the native protein. To investigate the behavior of these cells in vivo, we generated mice transgenic for a type B TCR recognizing the 48-62 epitope of hen egg white lysozyme (HEL) presented by I-Ak. Type B T cells responded only to peptide ex vivo, but responded in vivo to immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…Although peptides are small fragments of proteins, they can be presented quite differently, especially when loaded directly into empty surface class II molecules (19). Moreover, because many peptide vaccines are in clinical trials or have been approved for clinical applications (20,21), it is important to understand how exogenous peptides are loaded and presented.…”
Section: Discussionmentioning
confidence: 99%
“…Although peptides are small fragments of proteins, they can be presented quite differently, especially when loaded directly into empty surface class II molecules (19). Moreover, because many peptide vaccines are in clinical trials or have been approved for clinical applications (20,21), it is important to understand how exogenous peptides are loaded and presented.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly dramatic example of alternate peptide conformations comes from the work of Unanue and coworkers (21,25). They provide evidence that a single peptide, apparently bound in a fixed register, can have at least two conformations distinguished by different sets of T cells, depending on whether the peptide was loaded extracellularly (conformation A) or via the usual endocytic pathway (conformation B).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, we found that some of the peptides presented by DC under physiological conditions were susceptible to DM-mediated exchange, suggesting that they were generated through a processing pathway that did not include substantial exposure to DM (107,109,110). Although most peptides tested were relatively resistant to DM action, with DM resistance factors similar to or even greater than a high-affinity immunodominant viral epitope, several peptides were highly sensitive to DM action, with susceptibility values near that of CLIP, the canonical DM-susceptible fragment of the MHC II associated invariant chain removed by DM.…”
Section: Peptide Sourcementioning
confidence: 59%
“…Indeed, the eluted peptide with the highest ⌬IC 50 values among those tested (EAFQAMPPEELNK, ⌬IC 50 ϭ 0.160 M) derived from transforming growth factor-␤-induced protein IG-H3 (P82198), a secreted TGF␤3-induced protein that binds collagen in the extracellular matrix. Peptides derived from extracellular sources might load onto MHC II at the cell surface or intracellular locations with low DM activity and could represent a source of antigens for recognition by type B T cells (110). HLA-DM sensitivity and the fact that many of the MHC II-eluted peptides correspond to sequences known to be cleaved by extracellular proteases, such as complement 1, meprin, granzyme, MMPs, and ADAMS, point to the fact that the extracellular milieu/lymph is the likely source of many of the peptides eluted from HLA-DR1.…”
Section: Peptide Sourcementioning
confidence: 99%
See 1 more Smart Citation